EKSISTENSI LEMBAGA QUASI JUDISIAL DALAM SISTEM KEKUASAAN KEHAKIMAN DI INDONESIA : KAJIAN TERHADAP KOMISI PENGAWAS PERSAINGAN USAHA - Risnain, Muh (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Based on Indonesian Constitution 1945 the existence of quasi-judicial institution as a part of judicial power.Article 24 subsection (3 ) of the constitution of the republic of indonesia 1945 and the law number 48 / 2009 about judicial power admitting quasi-yudicial institutionshas judicial powers. For maximalize exercising of the quasi-judicial institutions are needed legal policy for supporting functional-constitusional relations between Commison for Supervion of Bussiness Competition and Supreme Court as top judicial power organization. Besides that needs to be done an effort to control the behavior commissioner of Commison For Supervion of Business Competition in avoiding abuse of power and moral hazard. These controlling must as part of power of Judicial Commission and Supreme Court. Keywords: Judicial Power, quasi-Judicial, Functional-constitutional and supervision